2007
DOI: 10.1021/bi061943x
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Picture of Atomic Motions within the Dickerson DNA Dodecamer in Solution Derived from Joint Ensemble Refinement against NMR and Large-Angle X-ray Scattering Data

Abstract: The structure and dynamics of the Dickerson DNA dodecamer [5′d(CGCGAATTCGCG) 2 ] in solution have been investigated by joint simulated annealing refinement against NMR and large-angle X-ray scattering data (extending from 0.25 to 3 Å -1 ). The NMR data comprise an extensive set of heteroand homonuclear residual dipolar coupling and 31 P chemical shift anisotropy restraints in two alignment media, supplemented by NOE and 3 J coupling data. The NMR and X-ray scattering data cannot be fully ascribed to a single s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
125
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(133 citation statements)
references
References 62 publications
8
125
0
Order By: Relevance
“…Recent success with combining NMR and SAXS/WAXS data for refining structural ensembles [32,[45][46][47] has shown that inclusion of global restraints is functionally complementary and successful for NMR structure solution, and our work shows that pump-probe X-ray scattering measurements have decisive value for time-resolved structure determination when used in combination with additional experimental restraints from DEER and NMR. b Ramachandran analysis was conducted on the calculated average structure from the ensemble using Molprobity (http://molprobity.biochem.duke.edu/).…”
Section: Interspin Distance and Distance Distribution Changes In The mentioning
confidence: 77%
“…Recent success with combining NMR and SAXS/WAXS data for refining structural ensembles [32,[45][46][47] has shown that inclusion of global restraints is functionally complementary and successful for NMR structure solution, and our work shows that pump-probe X-ray scattering measurements have decisive value for time-resolved structure determination when used in combination with additional experimental restraints from DEER and NMR. b Ramachandran analysis was conducted on the calculated average structure from the ensemble using Molprobity (http://molprobity.biochem.duke.edu/).…”
Section: Interspin Distance and Distance Distribution Changes In The mentioning
confidence: 77%
“…Second, there is a need to develop approaches for modulating alignment of nucleic acids. Only then will it be possible to effectively apply model-free 58,77 and ensemble 81 approaches for the characterization of dynamics with enhanced structural resolution. Finally, the combination of RDCs with other techniques, including spin-relaxation methods and timeresolved NMR discussed in other review articles in this issue promises to lay a basis for unraveling the structural plasticity of RNA over the entire window of biologically relevant timescales.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other NMR techniques, RDCs provide long-range angular structure information that helps to generate equilibrium ensemble models (9). In combination with molecular dynamic simulations, RDCs have been used to generate ensemble models for small disordered proteins (7,10), DNA duplexes (11), and a RNA bulge motif (12)(13)(14). In addition to RDCs, relaxation dispersion and paramagnetic relaxation enhancement have been used to detect and characterize conformational states that are in low abundance in an ensemble (5).…”
Section: Helix-junction-helix | Saxsmentioning
confidence: 99%